2022
DOI: 10.1007/s42486-022-00089-3
|View full text |Cite
|
Sign up to set email alerts
|

A survey on ubiquitous WiFi-based indoor localization system for smartphone users from implementation perspectives

Abstract: Indoor localization has the capability to change the way of providing location-based services in a closed environment and has more potential than that of GPS if the present shortcomings can be overcome. Thus, developing a ubiquitous Indoor Localization System (ILS) is the need of the day. WiFi-based indoor localization using smartphones is a promising approach to achieve ubiquity since smartphones are widely available today and most of the buildings are WiFi enabled. However, the significant variation of WiFi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 101 publications
0
15
0
Order By: Relevance
“…A combination of WiFi and fingerprinting technique can realize higher location accuracy, and pervasive infrastructures can be leveraged to reduce the investment. However, this solution is faced with the problems of excessive energy consumption and potential network congestion [23] . An ultra-wideband (UWB) system using the trilateration technique performs the best in terms of location accuracy as it can attain nearly 10-centimeter error [24] , but what hinders its further application should be the high cost and low scalability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A combination of WiFi and fingerprinting technique can realize higher location accuracy, and pervasive infrastructures can be leveraged to reduce the investment. However, this solution is faced with the problems of excessive energy consumption and potential network congestion [23] . An ultra-wideband (UWB) system using the trilateration technique performs the best in terms of location accuracy as it can attain nearly 10-centimeter error [24] , but what hinders its further application should be the high cost and low scalability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, as those systems rely on a single authentication factor, i.e., RSS measurements, it has been shown that they might be susceptible to a number of attacks [46]. Other works focus on a more precise localization [47]- [53]. To improve the performance most of these works rely on complex operations [50]- [53], (e.g.…”
Section: State Of the Art And Beyondmentioning
confidence: 99%
“…WLAN often operates according to the standard IEEE 802.11 at 2.4 GHz within the ISM band and has a range of about 50–100 m; however, the 5 GHz is now widely used for transmission due to less interference, less noise, higher constant connection, and higher speed [ 42 ].…”
Section: Signal Technologiesmentioning
confidence: 99%